PERANAN PERS UNTUK MEWUJUDKAN PERLINDUNGAN ANAK BERKELANJUTAN DI INDONESIA - Laurensius Arliman S (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
Children as part of a citizen, they have the same rights as other citizens, which shall be protected and respected by every citizen of the State. Child legal protection is defined as an effort to protect the law against freedom and child rights related to their welfare. Mass media coverage is adorned by the many acts of violence that occur in children. Today the phenomenon that occurs in the world of the press, the press media only focus more on democracy and politics and even the owners of the press media more focused plunge into the world of politics, even some owners of the press openly declare himself as a future presidential candidate or vice presidential candidate. The mass media should be required to broadcast appropriate information, for the development and protection of the rights of the child. Negative information will have a negative impact on the development of the child reaching his adult. The press in guarding the protection of children's rights, must carry out the role of social control and guarding every thing directly with children. This is because children are part of citizens, they have the same rights as other citizens, which must be protected and respected by every citizen and country.